Mania secondary to focal brain lesions: implications for understanding the functional neuroanatomy of bipolar disorder. (26th April 2016) - Satzer, David; Bond, David J
Abstract : Objectives: Approximately 3.5 million Americans will experience a manic episode during their lifetimes. The most common causes are psychiatric illnesses such as bipolar I disorder and schizoaffective disorder, but mania can also occur secondary to neurological illnesses, brain injury, or neurosurgical procedures. Methods: For this narrative review, we searched Medline for articles on the association of mania with stroke, brain tumors, traumatic brain injury, multiple sclerosis, neurodegenerative disorders, epilepsy, and neurosurgical interventions. We discuss the epidemiology, features, and treatment of these cases. We also review the anatomy of the lesions, in light of what is known about the neurobiology of bipolar disorder. Results: The prevalence of mania in patients with brain lesions varies widely by condition, from <2% in stroke to 31% in basal ganglia calcification. Mania occurs most commonly with lesions affecting frontal, temporal, and subcortical limbic brain areas. Right‐sided lesions causing hypo‐functionality or disconnection (e.g., stroke; neoplasms) and left‐sided excitatory lesions (e.g., epileptogenic foci) are frequently observed. Conclusions: Secondary mania should be suspected in patients with neurological deficits, histories atypical for classic bipolar disorder, and first manic episodes after the age of 40 years. Treatment with antimanic medications, along with specific treatment for the underlying neurologic condition, is typically required. Typical lesion locations fit with current models of bipolar disorder, which implicate hyperactivity of left‐hemisphere reward‐processing brain areas and hypoactivity of bilateral prefrontal emotion‐modulating regions. Lesion studies complement these models by suggesting that right‐hemisphere limbic‐brain hypoactivity, or a left/right imbalance, may be relevant to the pathophysiology of mania.